PENGARUH PEMBERDAYAAN SUMBER DAYA MANUSIA DAN KOMITMEN KERJA TERHADAP KINERJA KARYAWAN PT. MOLINDO INTI PERKASA MAKASSAR - Herlina, Herlina; Baso Amang; Muhammad Fadhil Hamzah; Burhanuddin, Burhanuddin (Bajang Institute, 2024)
The purpose of this research is to analyze the influence of human resource empowerment on the performance of PT employees. Molindo Inti Perkasa Makassar, and analyzing the influence of work commitment on the performance of PT employees. Molindo Inti Perkasa Makassar.This research was carried out at PT. Molindo Inti Perkasa Makassar, with a population and sample of all company employees of 65 respondents (full sampling). The data analysis used is descriptive to explain the research data, while to analyze quantitative data using the Multiple Linear Regression analysis tool. The research results prove that HR empowerment has a positive and significant effect on employee performance. This means that the company PT. Molindo Inti Perkasa Makassar always empowers its employees in the form of developing a shared vision, educating employees, improving employee skills, eliminating obstacles, expressing desires, providing encouragement, providing equipment/facilities, conducting evaluations and hoping for work success, which contributes to improving employee performance. Work commitment has a positive and insignificant effect on employee performance. This shows the employees of PT. Molindo Inti Perkasa Makassar has made efforts to be total in implementing the provisions that apply in the workplace, by pledging to advance the company where they work, comply with the rules that apply within the company and continuously demonstrate the achievements achieved by the company, but this still has not contributed to improving performance employees because they are not oriented towards achieving work results in terms of quantity, quality, efficiency, effectiveness and loyalty